Adaptation of welding transformer parameters taking into account arc output characteristics - Savchuk V. S.; Plekhov A. S. (Vestnik MGTU)
Widely used in modern technology welding of metals is a complex technological process. To assess the quality of a welded joint and its compliance with operational requirements, mathematical modeling methods are used. The mathematical model of a pulse transformer has been developed using the Matlab Simulink software package and software modules from Schneider Electric. The output data have been verified at the manufacturing company NPK Etalon (Rostov Region, Volgodonsk), where the obtained data have been compared with the theoretical base. The mathematical model of a pulse transformer allows implementing the STT (Surface Tension Transfer – heat and mass transfer due to the mechanism of surface tension forces) welding with a deeper calibration of current power pulses with clearly defined electrical parameters. It allows as well solving the problem of switching welding modes in complex operating scenarios; it is applicable to various types of welding (contact, arc, beam, etc.).